PENGGUNAAN STORYTELLING UNTUK PENDIDIKAN KARAKTER DALAM NOVEL AYAHKU (BUKAN) PEMBOHONG KARYA TERE LIYE - Murdianto Murdianto; Anis Rahmawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
Storytelling is an effective way to develop cognitive (knowledge), affective (feeling), and conative (appreciation) aspects in humans. The interaction of the father and Dam characters in the novel Ayahku (Not) the Liar provides an overview of the interaction between father and son, using the storytelling method in developing positive characters in children. The researcher conducted a search on the theme of storytelling for character education in the aspects of knowledge and attitude in the novel My Father (Not) Liar? This study uses a descriptive qualitative approach by using primary data sources for the novel entitled My Father (Not) Pembelian by Tere Liye, published by Gramedia Pustaka Utama, equipped with secondary data sources from documentation materials related to the theme and the novel with content analysis as an analytical technique. The results of this study The use of storytelling in character education in the knowledge aspect in Tere Liye's Father Not a Liar Novel is through 17 uses, while in the attitude aspect it is used 12 times.